Thymolipoma with massive pleural effusion: A case report - Bayramoğlu, Zeynep; Ömeroğlu, Ethem; Ünlü, Yaşar (Journal of Surgery and Medicine, 2019)
Thymolipoma is a rare and benign lesion originating from the anterior mediastinum. Thymolipoma is mostly diagnosed incidentally. However, cough, dyspnea and chest pain can be seen. A 35-year-old male patient presented to our hospital with the complaint of shortness of breath lasting for one month. The physical examination revealed a massive pleural effusion on the right. In computed tomography (CT) imaging of the thorax, a soft tissue density of 7.5x5x5 cm in size, containing calcifications were observed in the anterior mediastinum. A right thoracotomy was performed for the treatment and to make a definite diagnosis. The histopathological examination resulted in the diagnosis of a thymolipoma. We presented our case with its differential diagnosis because of its rarity.